Nano polycrystalline diamond and preparation method thereof
By performing high-temperature and high-pressure treatment on CVD polycrystalline diamond, it is first converted into nanographite and then into nanopolycrystalline diamond, the problem of uneven purity and structural unevenness of nanopolycrystalline diamond is solved, and the preparation of high purity colorless and transparent and excellent mechanical properties is achieved, expanding its application field.
Patent Information
- Application Number
- CN202510010520.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing nanopolycrystalline diamond has low purity, uneven nanostructures, and poor mechanical properties, resulting in poor transparency and limited application.
After encapsulating the CVD polycrystalline diamond with a wrapping material, it is first converted into nanographite and then converted into nanopolycrystalline diamond, achieving high purity and colorless transparency.
The high purity and colorless transparency of nano-polycrystalline diamond are achieved, with uniform structure, excellent optical and mechanical properties, and are widely used in optical window detection under extreme conditions.
Smart Images

Figure CN119800502A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of superhard materials, and in particular to a nano polycrystalline diamond and a preparation method thereof. Background Art
[0002] Diamond, also known as diamond, has the highest hardness, highest thermal conductivity, largest bandgap width, widest light transmittance band and other properties in nature. It is a multifunctional material with extremely excellent physical and chemical properties in force, heat, light, electricity, quantum and biomedicine.
[0003] Among the different types of diamond, nano-polycrystalline diamond (NPD) is a material composed of uniform nano-diamond particles, which are directly connected by diamond-diamond bonds to form a very dense structure. Compared with single-crystal diamond, nano-polycrystalline diamond has no anisotropy and dissociation characteristics, so it has higher hardness and better toughness. Due to its nano-scale particle size, nano-polycrystalline diamond has a very high grain boundary density, which can effectively prevent grain boundary slip, so it has extremely high wear resistance. The high hardness and wear resistance of nano-polycrystalline diamond make it an ideal material in the field of mechanical processing. It will play a greater role in high-pressure science, aerospace, biomedicine, environmental protection and other fields.
[0004] At present, there are two main methods for preparing nano-polycrystalline diamond bulk materials. One method mainly uses non-diamond powder carbon source to undergo phase change synthesis under high temperature and high pressure, such as using nano-graphite powder, amorphous carbon powder, carbon nanotubes, and fullerene onion carbon powder for pre-compression, and transforming them into nano-polycrystalline diamond at around 15-20GPa and 1800-2300℃. The other method is to use nano-diamond powder carbon source to directly sinter and synthesize under high temperature and high pressure.
[0005] Although these graphite powders or nano-diamond powders are subjected to vacuum heat treatment or pickling treatment during the preparation process, due to the high activity of nanomaterials and strong surface adsorption capacity, they will inevitably come into contact with air during the preparation process, introducing impurities. In addition, these powders already contain a large amount of nitrogen impurities inside the crystals during production, which cannot be eliminated by subsequent treatment methods. As a result, the transparency of NPD currently prepared using graphite powder or diamond powder is poor. Due to the absorption of a large amount of nitrogen impurities in the visible light band, it appears brownish yellow instead of colorless and transparent. These defects seriously limit the widespread application of NPD.
[0006] Polycrystalline diamond with high purity can be synthesized by chemical vapor deposition (CVD). However, due to the deposition method of the CVD method, the grain size of the CVD diamond nucleation surface and the growth surface are inconsistent, the columnar crystals are obvious, and a uniform nanostructure cannot be formed. In addition, the synthesized diamond has large internal stress and poor mechanical properties. Summary of the invention
[0007] The purpose of the present application is to provide a nano-polycrystalline diamond and a preparation method thereof, aiming to solve the problems of low purity, uneven nanostructure and poor mechanical properties of existing nano-polycrystalline diamond.
[0008] To achieve the above objectives, the present application provides a method for preparing nano-polycrystalline diamond, comprising:
[0009] The CVD polycrystalline diamond is packaged with a wrapping material, a heating material, a heat-insulating material and a pressure-transmitting medium in sequence to obtain a synthetic block and then baked;
[0010] The baked synthetic block is subjected to a first treatment at a first pressure and a first temperature to obtain nanographite;
[0011] Performing a second treatment on the nanographite at a second pressure and a second temperature to obtain nano-polycrystalline diamond;
[0012] The second pressure is greater than the first pressure.
[0013] In some embodiments, the first pressure is 1 GPa to 4 GPa; the second pressure is 15 GPa to 25 GPa.
[0014] In some embodiments, the first temperature is 1800°C to 2200°C; the second temperature is 2000°C to 2400°C.
[0015] In some embodiments, the first treatment lasts for 20 min to 60 min; the second treatment lasts for 1 min to 20 min.
[0016] In some embodiments, the pressure is first increased to the first pressure, then heated to the first temperature, and the heating is turned off after the first processing time is reached; the first pressure is further increased to the second pressure, and then heated to the second temperature, and the temperature and pressure are reduced after the second processing time is reached.
[0017] In some embodiments, the baking temperature is 80-200° C., and the baking time is 4-8 hours.
[0018] In some embodiments, the encapsulating material is selected from any one of graphite, hexagonal boron nitride, cubic boron nitride, NaCl, CsCl, gold, and platinum; and the purity of the encapsulating material is greater than 99%.
[0019] In some embodiments, the heating material is selected from any one of a graphite tube, a tantalum tube, a rhenium tube, and a rhenium chromate tube; the thermal insulation material is selected from any one of zirconium oxide, a rhenium chromate tube, and a zirconium oxide doped with calcium oxide tube; the pressure transmission medium is selected from any one of MgO element, magnesium oxide doped with cobalt trioxide, and magnesium oxide doped with chromium oxide.
[0020] In some embodiments, the CVD polycrystalline diamond is prepared in a chemical vapor deposition growth device, hydrogen and methane are introduced, the pressure in the chamber is controlled at 12KPa to 15KPa, the temperature is controlled at 800°C to 1200°C, the volume ratio of methane to hydrogen is 3% to 15%, and the area of the polycrystalline substrate is 20 to 80mm 2 , the growth thickness is 1 to 5 mm.
[0021] The present application also provides a nano-polycrystalline diamond, which is prepared by the above-mentioned method for preparing nano-polycrystalline diamond.
[0022] Compared with the prior art, the beneficial effects of this application include:
[0023] The preparation method of nano-polycrystalline diamond provided in the present application first uses a high-purity, low-impurity CVD polycrystalline diamond / diamond-like carbon block grown by chemical vapor deposition as an initial sample. Since CVD polycrystalline diamond is synthesized by reaction in a vacuum environment, no internal impurities are introduced. The CVD polycrystalline diamond is further converted into a nano-polycrystalline graphite block through a first treatment at high temperature and medium pressure, and then the pressure and temperature are increased in situ to the high temperature and high pressure environment required for the conversion of graphite into diamond for a second treatment, thereby obtaining a high-purity, colorless and transparent nano-polycrystalline diamond.
[0024] The nano-polycrystalline diamond prepared by the process of the present application has a uniform structure, high purity, and excellent optical and mechanical properties; it can be widely used in optical window detection under extreme conditions, such as X-ray optical absorption under ultra-high pressure; the method of the present application is simple and reliable, highly safe, low-cost, and widely used, and can realize large-scale production of high-purity nano-polycrystalline diamond.
[0025] The nanographite block prepared by the method of the present application is obtained by phase transformation of a CVD block, thereby avoiding the contamination of the powder in the air, and having pure grain boundaries and high purity. The CVD block prepared by the method of the present application is synthesized by gas reaction in a vacuum chamber, and the content of nitrogen impurities during the growth process can be controlled below the ppm level, thereby solving the problem of the brown-yellow color caused by high-temperature and high-pressure sintering of direct nanodiamond powder, thereby obtaining colorless and transparent nano polycrystalline diamond, and widely improving its application field. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0027] Figure 1 A schematic diagram of the process of preparing nano-polycrystalline diamond of the present application;
[0028] Figure 2 This is a schematic diagram of the structure of the synthesis block of this application;
[0029] Figure 3 A graph showing changes in pressure and temperature in the method for preparing nano-polycrystalline diamond of the present application;
[0030] Figure 4 Raman spectrum of CVD polycrystalline diamond prepared by chemical vapor deposition;
[0031] Figure 5 This is the Raman spectrum of nanographite cylinders after high temperature and medium pressure graphitization of CVD polycrystalline diamond;
[0032] Figure 6 is the SEM image of nanographite cylinder;
[0033] Figure 7 XRD spectra of CVD single crystal diamond and CVD polycrystalline diamond after graphitization;
[0034] Figure 8 The actual pictures are two different specifications of graphitized nanographite cylinders;
[0035] Fig. 9 This is a physical comparison of a 3mm nanographite cylinder and a converted colorless and transparent nanopolycrystalline diamond;
[0036] Fig.10 This is the infrared absorption spectrum of the colorless and transparent nano-polycrystalline diamond prepared in Example 3;
[0037] Fig.11 The Vickers hardness indentation diagram of CVD diamond and prepared colorless and transparent nano-polycrystalline diamond.
[0038] Reference numerals:
[0039] 10-CVD polycrystalline diamond; 20-wrapping material; 30-heating material; 40-heat insulation material; 50-pressure transmission medium. DETAILED DESCRIPTION
[0040] As used herein:
[0041] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0042] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0043] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0044] In these examples, parts and percentages are by mass unless otherwise indicated.
[0045] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0046] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0047] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0048] This application provides a method for preparing nano polycrystalline diamond. Figure 1 ,include:
[0049] S100: encapsulating the CVD polycrystalline diamond with a wrapping material, a heating material, a heat-insulating material and a pressure-transmitting medium in sequence to obtain a synthetic block and baking the block;
[0050] S200: performing a first treatment on the baked synthetic block at a first pressure and a first temperature to obtain nanographite;
[0051] S300: performing a second treatment on the nanographite at a second pressure and a second temperature to obtain nano-polycrystalline diamond; wherein the second pressure is greater than the first pressure.
[0052] This application first uses a high-purity, low-impurity CVD polycrystalline diamond / diamond-like carbon block grown by chemical vapor deposition as the initial sample. Since CVD polycrystalline diamond is synthesized by reaction in a vacuum environment, no internal impurities will be introduced; the CVD polycrystalline diamond is further converted into a nano-polycrystalline graphite block by a first treatment of high temperature and medium pressure, and then the pressure and temperature are raised in situ to the high temperature and high pressure environment required for graphite to be converted into diamond for a second treatment, so that high-purity, colorless and transparent nano-polycrystalline diamond can be obtained. The nano-polycrystalline diamond prepared by the process of this application has a uniform structure, high purity, and excellent optical and mechanical properties; it can be widely used in optical window detection under extreme conditions, such as X-ray optical absorption under ultra-high pressure; the method of this application is simple and reliable, highly safe, low cost, and widely used, and can achieve large-scale production of high-purity nano-polycrystalline diamond.
[0053] The nanographite block prepared by the method of the present application is obtained by phase transformation of a CVD block, thereby avoiding the contamination of the powder in the air, and having pure grain boundaries and high purity. The CVD block prepared by the method of the present application is synthesized by gas reaction in a vacuum chamber, and the content of nitrogen impurities during the growth process can be controlled below the ppm level, thereby solving the problem of the brown-yellow color caused by high-temperature and high-pressure sintering of direct nanodiamond powder, thereby obtaining colorless and transparent nano polycrystalline diamond, and widely improving its application field.
[0054] The CVD polycrystalline diamond in step S100 refers to polycrystalline diamond prepared by chemical vapor deposition (CVD). The CVD polycrystalline diamond can be prepared by itself or purchased from the market as required. Since CVD polycrystalline diamond is synthesized by reaction in a vacuum environment, no internal impurities are introduced. The nitrogen content of the initial CVD polycrystalline diamond / diamond-like carbon is adjusted to be below the ppm level by controlling the content of the nitrogen source gas during vapor deposition.
[0055] Among them, see Figure 2 The CVD polycrystalline diamond 10 is packaged with a wrapping material 20, a heating material 30, a heat-insulating material 40 and a pressure-transmitting medium 50 in sequence, assembled under high temperature and high pressure to obtain a synthetic block and baked for subsequent high temperature and high pressure treatment.
[0056] In some embodiments, the baking temperature of step S100 is 80-200°C, for example, it can be 80°C, 100°C, 120°C, 150°C, 170°C, 200°C or any value between 80 and 200°C, and the baking time is 4 to 8 hours, for example, it can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or any value between 4 and 8 hours.
[0057] In some embodiments, the wrapping material in step S100 is selected from any one of graphite, hexagonal boron nitride, cubic boron nitride, NaCl, CsCl, gold, and platinum; the purity of the wrapping material is greater than 99%. The wrapping material is preferably a material with good hydrostatic pressure (fluid or quasi-fluid state under high temperature and high pressure) and stable performance (no reaction with carbon under high temperature and high pressure, or only a trace reaction).
[0058] In some embodiments, the heating material of step S100 is selected from any one of a graphite tube, a tantalum tube, a rhenium tube, and a rhenium chromate tube; the insulation material is selected from any one of zirconium oxide, a rhenium chromate tube, and a zirconium oxide doped with calcium oxide tube; the pressure transmission medium is selected from any one of MgO element, magnesium oxide doped with cobalt trioxide, and magnesium oxide doped with chromium oxide.
[0059] In some embodiments, the CVD polycrystalline diamond of step S100 is prepared in a chemical vapor deposition growth device, hydrogen and methane are introduced, the pressure in the chamber is controlled at 12KPa to 15KPa, the temperature is controlled at 800°C to 1200°C, the volume ratio of methane to hydrogen is 3% to 15%, and the area of the polycrystalline substrate is 20 to 80mm 2 , the growth thickness is 1 to 5 mm.
[0060] Among them, the matching of the pressure and temperature of the first pressure of step S200 is located outside the stable zone of the diamond phase, and it is necessary to ensure that the CVD polycrystalline diamond / diamond-like carbon block will undergo obvious graphitization at high temperature. When the pressure is high, the graphitization temperature also needs to be increased accordingly. The first pressure can be medium pressure, generally less than 5GPa. In another way, the CVD polycrystalline diamond / diamond-like carbon block can also be subjected to vacuum high-temperature graphitization under normal pressure to obtain a nanographite block. At this time, the first pressure is normal pressure, but this method has a longer production cycle. The second pressure is high temperature and high pressure, and it is necessary to ensure that the nanographite block can be transformed into nano polycrystalline diamond.
[0061] In some embodiments, the first pressure of step S200 is 1 GPa to 4 GPa, for example, it can be 1 GPa, 2 GPa, 3 GPa, 4 GPa or any value between 1 GPa and 4 GPa.
[0062] In some embodiments, the first temperature of step S200 is 1800°C to 2200°C, for example, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C or any value between 1800°C and 2200°C.
[0063] In some embodiments, the time of the first processing in step S200 is 20 min to 60 min, for example, it can be 20 min, 30 min, 40 min, 50 min, 60 min or any value between 20 min and 60 min.
[0064] In some embodiments, the second pressure of step S300 is 15 GPa to 25 GPa, for example, it can be 15 GPa, 16 GPa, 17 GPa, 18 GPa, 19 GPa, 20 GPa, 21 GPa, 22 GPa, 23 GPa, 24 GPa, 25 GPa or any value between 15 GPa and 25 GPa.
[0065] In some embodiments, the second temperature of step S300 is 2000°C to 2400°C, for example, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C or any value between 2000°C and 2400°C.
[0066] In some embodiments, the time of the second processing in step S300 is 1 min to 20 min, for example, it can be 1 min, 5 min, 10 min, 15 min, 20 min or any value between 1 min and 20 min.
[0067] In some embodiments, see Figure 3 The process settings of pressure and temperature of the method of the present application are: first increase the pressure to a first pressure, then heat to a first temperature, and turn off the heating after the first processing time is reached; continue to increase the first pressure to a second pressure in situ, then heat to a second temperature, and cool and reduce the pressure to normal temperature and pressure after the second processing time is reached.
[0068] The present application also provides a nano-polycrystalline diamond, which is prepared by the above-mentioned method for preparing nano-polycrystalline diamond.
[0069] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0070] In the following embodiments and comparative examples, the large-cavity static high-pressure device is a 2000-ton Kawai two-sided top press and a domestic six-sided top press, and the CVD polycrystalline diamond / diamond-like carbon block material is prepared by direct current arc or microwave plasma chemical vapor deposition.
[0071] In the following embodiments and comparative examples, the heating material is a rhenium tube, the heat-insulating material is zirconium oxide, and the pressure-transmitting medium is MgO.
[0072] Example 1
[0073] This embodiment provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0074] (1) Initial sample preparation
[0075] In the chemical vapor deposition growth equipment, hydrogen and methane are introduced, the pressure in the chamber is controlled at 13KPa, the temperature is controlled at 950℃, the volume ratio of methane / hydrogen is generally 8%, and the area of the polycrystalline substrate is 50mm 2 The deposition rate of polydiamond can be adjusted by controlling the gas pressure in the chamber, the ratio of mixed gas, substrate temperature, heating power, etc. The growth thickness is about 2mm. After deposition, the laser is cut into 3mm CVD polycrystalline diamond cylinders as the carbon source for NPD synthesis.
[0076] (2) Package selection
[0077] Hexagonal boron nitride is selected as the packaging material to provide a hydrostatic pressure environment, and necessary drying and purification treatment is performed before use to remove moisture and impurities. The purity of the packaging material is greater than 99%.
[0078] (3) Synthetic block baking
[0079] The processed CVD polycrystalline diamond cylinder and the external wrapping material are integrally placed in the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 120° C. for 4 hours.
[0080] (4) Graphitization treatment and high temperature and high pressure synthesis
[0081] The baked synthetic block is directly placed in a high temperature and high pressure device. First, it is treated at high temperature and medium pressure for 20 minutes under the conditions of pressure 4GPa and temperature 2000℃. The CVD polycrystalline diamond cylinder undergoes a graphitization phase change at high temperature and is transformed into a nanographite cylinder. After the treatment time is reached, it is treated at high temperature and high pressure for 5 minutes under the conditions of pressure 15GPa and temperature 2100℃ to convert the nanographite cylinder into a nano-polycrystalline diamond. The surface inclusions are removed by washing with mixed acid at 200℃ for 3 hours, and then the impurities adsorbed on the surface are ultrasonically removed with alcohol and deionized water. After the surface is precisely polished, the high-purity colorless and transparent nano-polycrystalline diamond of Example 1 is obtained. However, the nano-polycrystalline diamond prepared by directly sintering nano-diamond powder at high temperature and high pressure under the same pressure of 15GPa and temperature 2100℃ is only partially transparent and presents a brownish yellow color, indicating that its purity is poor.
[0082] The temperature and pressure rise and fall process conditions are as follows: the pressure is raised to 4 GPa at a pressure rise rate of 10 GPa / h, and then the pressure is kept constant, and then the temperature is raised to 2000°C at a heating rate of 200°C / min and kept at this temperature for 20 minutes. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200°C / min, and then the pressure is raised to 15 GPa at a pressure rise rate of 3 GPa / h. Secondary heating is performed, the temperature is raised to 2100°C at a heating rate of 200°C / min and kept at this temperature for 5 minutes. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200°C / min, and then the pressure is lowered to normal pressure at a pressure drop rate of 2 GPa / h.
[0083] Figure 4 The Raman spectrum of CVD polycrystalline diamond prepared by chemical vapor deposition shows that the main component is diamond before graphitization. Figure 5 This is the Raman spectrum of nanographite cylinder after high-temperature and medium-pressure graphitization of CVD polycrystalline diamond, which is a standard graphite Raman peak. Figure 6 This is the SEM image of nanographite cylinders. Figure 7 Figure 2 is the XRD spectra of CVD single crystal diamond and CVD polycrystalline diamond after graphitization, which are standard graphite diffraction peaks, indicating that CVD diamond has been completely converted into graphite crystals under medium pressure and high temperature.
[0084] Example 2
[0085] This embodiment provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0086] (1) Initial sample preparation
[0087] In the chemical vapor deposition growth equipment, hydrogen and methane are introduced, the pressure in the chamber is controlled at 15KPa, the temperature is controlled at 1200℃, the ratio of methane to hydrogen is generally 15%, and the area of the polycrystalline substrate is 20mm2 The growth thickness is about 3 mm. After deposition, the deposited polycrystalline diamond cylinders are cut into 3 mm CVD-type diamond cylinders by laser and used as carbon source for NPD synthesis.
[0088] (2) Package selection
[0089] Hexagonal boron nitride tubes are selected as wrapping materials to provide a hydrostatic environment, and necessary drying and purification treatments are performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0090] (3) Synthetic block baking
[0091] The processed CVD polycrystalline diamond cylinder and the external wrapping material are integrally placed in the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 150° C. for 6 hours.
[0092] (4) Graphitization treatment and high temperature and high pressure synthesis
[0093] The baked synthetic block is directly placed in a high temperature and high pressure device. First, it is treated at high temperature and medium pressure for 30 minutes under the conditions of pressure 2GPa and temperature 1900°C. The CVD polycrystalline diamond cylinder undergoes a graphitization phase transition at high temperature and is transformed into a nano-graphite cylindrical block. After the treatment time is reached, it is treated at high temperature and high pressure for 5 minutes under the conditions of pressure 16GPa and temperature 2200°C. The nano-graphite cylinder is converted into nano-polycrystalline diamond. Wash with mixed acid at 200°C for 3 hours to remove surface inclusions, and then use alcohol and deionized water to ultrasonically remove impurities adsorbed on the surface. After the surface is precisely polished, the high-purity colorless and transparent nano-polycrystalline diamond of Example 2 is obtained.
[0094] The temperature and pressure rise and fall process conditions are as follows: the pressure is raised to 2GPa at a pressure rise rate of 8GPa / h, and then the pressure is kept constant. Then the temperature is raised to 1900℃ at a heating rate of 200℃ / min and kept at this temperature for 20min. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200℃ / min, and then the pressure is raised to 16GPa at a pressure rise rate of 5GPa / h. Secondary heating is performed, the temperature is raised to 2200℃ at a heating rate of 200℃ / min and kept at this temperature for 5min. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200℃ / min, and then the pressure is lowered to normal pressure at a pressure drop rate of 3GPa / h.
[0095] Example 3
[0096] This embodiment provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0097] (1) Initial sample preparation
[0098] Commercially available CVD polycrystalline diamond prepared by direct current arc was used, with a thickness of 1.5 mm after double-side polishing and laser cut into cylinders with a diameter of 3 mm as the carbon source for NPD synthesis.
[0099] (2) Package selection
[0100] The magnesium oxide tube is selected as the wrapping material to provide a hydrostatic pressure environment, and necessary drying and purification treatment is performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0101] (3) Synthetic block baking
[0102] The processed CVD polycrystalline diamond cylinder and the external wrapping material are integrally placed in the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 120° C. for 2 hours.
[0103] (4) Graphitization treatment and high temperature and high pressure synthesis
[0104] The baked synthetic block is directly placed in a six-sided high-temperature and high-pressure device. First, it is treated at high temperature and medium pressure for 30 minutes under the conditions of pressure 3GPa and temperature 2000℃. The CVD polycrystalline diamond cylinder undergoes a graphitization phase change at high temperature and is transformed into a nanographite cylinder. After the treatment time is reached, the nanographite cylinder is taken out and placed in a two-stage press on the two sides. It is treated at high temperature and high pressure for 5 minutes under the conditions of pressure 15GPa and temperature 2300℃ to transform the nanographite cylinder into nano-polycrystalline diamond. It is washed with mixed acid at 200℃ for 3 hours to remove the surface inclusions, and then alcohol and deionized water are used to ultrasonically remove the impurities adsorbed on the surface. After the surface is precisely polished, the high-purity colorless and transparent nano-polycrystalline diamond of Example 3 is obtained.
[0105] The temperature and pressure rise and fall process conditions are as follows: the pressure is raised to 3GPa at a pressure rise rate of 10GPa / h, and then the pressure is kept constant, and then the temperature is raised to 2000℃ at a heating rate of 200℃ / min and kept at this temperature for 30min. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200℃ / min, and then the pressure is raised to 15GPa at a pressure rise rate of 5GPa / h in a double-sided top press. Secondary heating is performed, the temperature is raised to 2300℃ at a heating rate of 200℃ / min and kept at this temperature for 5min. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200℃ / min, and then the pressure is lowered to normal pressure at a pressure reduction rate of 3GPa / h.
[0106] Figure 8 Actual pictures of two different specifications of nanographite cylinders after graphitization. Fig. 9 This is a physical comparison picture of a 3mm nanographite cylinder and a converted colorless and transparent nano-polycrystalline diamond. Fig.10The infrared absorption spectrum of the prepared colorless and transparent nano polycrystalline diamond is shown in FIG. No absorption peak appears at 1000-1500 wave numbers, indicating that a large amount of nitrogen impurities are not introduced into the NPD prepared by the method of the present application, resulting in a brown tone. Fig.11 The Vickers hardness indentation diagrams of the initial CVD diamond (a) and the prepared colorless and transparent nano-polycrystalline diamond (b) show that the hardness of the initial CVD diamond is about 80 GPa, and the cracks are obvious, while the nano-polycrystalline diamond transformed from graphitized CVD nano-graphite has a hardness of about 115 GPa due to grain refinement and more dense sintering. Due to the high hardness value, the indenter of the hardness tester is easily damaged during the measurement process.
[0107] Example 4
[0108] This embodiment provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0109] (1) Initial sample preparation
[0110] Commercially available CVD polycrystalline diamond prepared by direct current arc was used, with a thickness of 2 mm after double-side polishing and laser cut into cylinders with a diameter of 5 mm as the carbon source for NPD synthesis.
[0111] (2) Package selection
[0112] Hexagonal boron nitride tubes are selected as wrapping materials to provide a hydrostatic environment, and necessary drying and purification treatments are performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0113] (3) Synthetic block baking
[0114] The processed CVD polycrystalline diamond cylinder and the external wrapping material are integrally placed in the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 120° C. for 4 hours.
[0115] (4) Graphitization treatment and high temperature and high pressure synthesis
[0116] The baked synthetic block is directly placed in a six-sided high-temperature and high-pressure device. First, it is treated at high temperature and medium pressure for 20 minutes under a pressure of 2GPa and a temperature of 2200°C. The CVD polycrystalline diamond cylinder undergoes a graphitization phase change at high temperature and is transformed into a nanographite cylinder. After the treatment time is reached, the nanographite cylinder is processed into a 3.5mm diameter cylinder, placed in a two-stage press on the two sides, and treated at high temperature and high pressure for 5 minutes under a pressure of 16GPa and a temperature of 2300°C again to convert the CVD type nanographite cylinder into nano-polycrystalline diamond. The surface is cleaned at 200°C for 3 hours to remove the surface inclusions, and then the impurities adsorbed on the surface are ultrasonically removed with alcohol and deionized water. After the surface is precisely polished, the high-purity colorless and transparent nano-polycrystalline diamond of Example 4 is obtained.
[0117] The temperature and pressure rise and fall process conditions are as follows: the pressure is raised to 2GPa at a pressure rise rate of 10GPa / h, and then the pressure is kept constant, and then the temperature is raised to 2200℃ at a heating rate of 200℃ / min and kept at this temperature for 20min. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200℃ / min, and then the pressure is raised to 16GPa at a pressure rise rate of 5GPa / h in a double-sided top press. Secondary heating is performed, the temperature is raised to 2300℃ at a heating rate of 200℃ / min and kept at this temperature for 5min. After the treatment time is reached, the temperature is first lowered to room temperature at a cooling rate of 200℃ / min, and then the pressure is lowered to normal pressure at a pressure reduction rate of 3GPa / h.
[0118] Comparative Example 1
[0119] This comparative example provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0120] (1) Initial sample preparation
[0121] Commercially available CVD polycrystalline diamond prepared by direct current arc was used, with a thickness of 1.5 mm after double-side polishing and laser cut into cylinders with a diameter of 3 mm as the carbon source for NPD synthesis.
[0122] (2) Package selection
[0123] Hexagonal boron nitride tubes are selected as wrapping materials to provide a hydrostatic environment, and necessary drying and purification treatments are performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0124] (3) Synthetic block baking
[0125] The processed CVD polycrystalline diamond cylinder and the external wrapping material are integrally placed in the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 120° C. for 2 hours.
[0126] (4) Direct high temperature and high pressure treatment
[0127] The baked synthetic block was directly placed in a six-sided high-temperature and high-pressure device and treated at a pressure of 15GPa and a temperature of 1900℃ for 5 minutes. The surface inclusions were removed by washing with mixed acid at 200℃ for 3 hours, and then the impurities adsorbed on the surface were ultrasonically removed with alcohol and deionized water. After precision polishing, the surface was obtained to obtain optically transparent CVD polycrystalline diamond. However, due to the lack of re-phase transformation after graphitization at high temperature and medium pressure, the grain size of polycrystalline diamond did not change significantly, the grain size was large, and the mechanical properties were poor. The hardness value is 80GPa, which is much lower than the 120GPa hardness of nano-polycrystalline diamond.
[0128] Comparative Example 2
[0129] This comparative example provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0130] (1) Initial sample preparation
[0131] Commercially available CVD polycrystalline diamond prepared by direct current arc was used, with a thickness of 2 mm after double-side polishing and laser cut into cylinders with a diameter of 3 mm as the carbon source for NPD synthesis.
[0132] (2) Package selection
[0133] Hexagonal boron nitride tubes are selected as wrapping materials to provide a hydrostatic environment, and necessary drying and purification treatments are performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0134] (3) Synthetic block baking
[0135] The processed CVD polycrystalline diamond cylinder and the external wrapping material are placed as a whole into the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 150° C. for 1 hour.
[0136] (4) Graphitization treatment and high temperature and high pressure synthesis
[0137] The baked synthetic block was directly placed in a six-sided high-temperature and high-pressure device. First, it was treated at high temperature and medium pressure for 20 minutes at a pressure of 2GPa and a temperature of 2200℃. The CVD polycrystalline diamond cylinder underwent a graphitization phase transition at high temperature and turned into a nanographite cylinder. After the treatment time was reached, the graphite cylinder was placed in a two-stage press on the two sides, and was treated at high temperature and high pressure for 5 minutes at a pressure of 13GPa and a temperature of 1700℃ to convert the CVD nanographite cylinder into nano-polycrystalline diamond. The surface was cleaned with mixed acid at 200℃ for 3 hours to remove the surface coating, and then the impurities adsorbed on the surface were ultrasonically removed with alcohol and deionized water. After the surface was precisely polished, no colorless and transparent nano-polycrystalline diamond was obtained. After X-ray testing, the synthesized opaque nano-polycrystalline diamond contained obvious graphite peaks, indicating that due to insufficient pressure and temperature, some graphite was not completely converted into nano-polycrystalline diamond.
[0138] Comparative Example 3
[0139] This comparative example provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0140] (1) Initial sample preparation
[0141] Commercially available CVD polycrystalline diamond prepared by direct current arc was used, with a thickness of 2 mm after double-side polishing and laser cut into cylinders with a diameter of 5 mm as the carbon source for NPD synthesis.
[0142] (2) Package selection
[0143] Hexagonal boron nitride tubes are selected as wrapping materials to provide a hydrostatic environment, and necessary drying and purification treatments are performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0144] (3) Synthetic block baking
[0145] The processed CVD polycrystalline diamond cylinder and the external wrapping material are placed as a whole into the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 150° C. for 1 hour.
[0146] (4) Graphitization treatment
[0147] The baked synthetic block was directly placed in a six-sided high-temperature and high-pressure device, and first treated at a high temperature and medium pressure of 5GPa and 1300℃ for 20 minutes. After the treatment time was reached, the CVD polycrystalline diamond cylinder did not undergo a graphitization phase transition at this pressure and temperature, and remained in the initial CVD diamond structure. This is mainly due to the mismatch of pressure and temperature conditions, and it is still in the stable zone of the diamond phase, and the diamond cannot be graphitized.
[0148] Comparative Example 4
[0149] This comparative example provides a nano-polycrystalline diamond, and the preparation method thereof comprises the following steps:
[0150] (1) Initial sample preparation
[0151] Commercially available CVD polycrystalline diamond prepared by direct current arc was used, with a thickness of 2 mm after double-side polishing and laser cut into cylinders with a diameter of 3 mm as the carbon source for NPD synthesis.
[0152] (2) Package selection
[0153] Hexagonal boron nitride tubes are selected as wrapping materials to provide a hydrostatic environment, and necessary drying and purification treatments are performed before use to remove moisture and impurities. The purity of the wrapping material is greater than 99%.
[0154] (3) Synthetic block baking
[0155] The processed CVD polycrystalline diamond cylinder and the external wrapping material are placed as a whole into the nested pressure transmission medium, heat insulation material and heating material to form a synthetic block, and the synthetic block is baked in a muffle furnace or oven at 150° C. for 1 hour.
[0156] (4) Graphitization treatment
[0157] The baked synthetic block was directly placed in a six-sided high-temperature and high-pressure device, and first treated at a high temperature and medium pressure of 10GPa and 1700℃ for 20 minutes. After the treatment time was reached, the CVD polycrystalline diamond cylinder did not undergo a graphitization phase transition at this pressure and temperature, and remained in the initial CVD diamond structure. This is mainly due to the mismatch of pressure and temperature conditions, and it is still in the stable zone of the diamond phase, and the diamond cannot be graphitized.
[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0159] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing nano polycrystalline diamond, characterized in that: include: The CVD polycrystalline diamond is packaged with a wrapping material, a heating material, a heat-insulating material and a pressure-transmitting medium in sequence to obtain a synthetic block and then baked; The baked synthetic block is subjected to a first treatment at a first pressure and a first temperature to obtain nanographite; Performing a second treatment on the nanographite at a second pressure and a second temperature to obtain nano-polycrystalline diamond; The second pressure is greater than the first pressure.
2. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The first pressure is 1 GPa to 4 GPa; the second pressure is 15 GPa to 25 GPa.
3. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The first temperature is 1800°C to 2200°C; the second temperature is 2000°C to 2400°C.
4. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The time of the first treatment is 20 minutes to 60 minutes; the time of the second treatment is 1 minute to 20 minutes.
5. The method for preparing nano-polycrystalline diamond according to any one of claims 1 to 4, characterized in that: First, the pressure is increased to the first pressure, and then heated to the first temperature. After the first processing time is reached, the heating is turned off; the first pressure is further increased to the second pressure, and then heated to the second temperature. After the second processing time is reached, the temperature and pressure are reduced.
6. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The baking temperature is 80-200° C., and the baking time is 4-8 hours.
7. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The wrapping material is selected from any one of graphite, hexagonal boron nitride, cubic boron nitride, NaCl, CsCl, gold and platinum; and the purity of the wrapping material is greater than 99%.
8. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The heating material is selected from any one of graphite tube, tantalum tube, rhenium tube and rhenium chromate tube; the insulation material is selected from any one of zirconium oxide, rhenium chromate tube and zirconium oxide doped with calcium oxide tube; the pressure transmission medium is selected from any one of MgO single substance, magnesium oxide doped with cobalt trioxide and magnesium oxide doped with chromium oxide.
9. The method for preparing nano polycrystalline diamond according to claim 1, characterized in that: The CVD polycrystalline diamond is prepared in a chemical vapor deposition growth device, hydrogen and methane are introduced, the pressure in the chamber is controlled at 12KPa-15KPa, the temperature is controlled at 800°C-1200°C, the volume ratio of methane / hydrogen is 3%-15%, and the area of the polycrystalline substrate is 20-80mm 2 , the growth thickness is 1 to 5 mm.
10. A nano polycrystalline diamond, characterized in that: The nano polycrystalline diamond is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Cited By
Preparation process of high-quality synthetic diamond
CN120437891A
A high-quality synthetic diamond production process
CN120437891B
Cubic boron nitride-nano polycrystalline diamond composite material and preparation method thereof
CN121872777A
Hexagonal boron nitride-nano polycrystalline diamond composite material and preparation method thereof
CN121974695A